T5 law and Matthiessen's rule - Bressan, O.J.; Ridner, A.E.; de la Cruz, F. (IOP Publishing, 1975)
Fil: Bressan, O.J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina